β-amyloid inhibits protein prenylation and induces cholesterol sequestration by impairing SREBP-2 cleavage - Mohamed, Amany (2012)
Accumulation of β-amyloid (Aβ) inside brain neurons is an early and crucial event in Alzheimer's disease (AD). Studies in brains of AD patients and mice models of AD suggested that cholesterol homeostasis is altered in neurons that accumulate Aβ. Here we directly investigated the role of intracellular oligomeric Aβ(42) (oAβ(42)) in neuronal cholesterol homeostasis. We report that oAβ(42) induces cholesterol sequestration without increasing cellular cholesterol mass. Several features of AD, such as endosomal abnormalities, brain accumulation of Aβ and neurofibrillary tangles, and influence of apolipoprotein E genotype, are also present in Niemann-Pick type C, a disease characterized by impairment of intracellular cholesterol trafficking. These common features and data presented here suggest that a pathological mechanism involving abnormal cholesterol trafficking could take place in AD. Cholesterol sequestration in Aβ-treated neurons results from impairment of intracellular cholesterol trafficking secondary to inhibition of protein prenylation. oAβ(42) reduces sterol regulatory element-binding protein-2 (SREBP-2) cleavage, causing decrease of protein prenylation. Inhibition of protein prenylation represents a mechanism of oAβ(42)-induced neuronal death. Supply of the isoprenoid geranylgeranyl pyrophosphate to oAβ(42)-treated neurons recovers normal protein prenylation, reduces cholesterol sequestration, and prevents Aβ-induced neurotoxicity. Significant to AD, reduced levels of protein prenylation are present in the cerebral cortex of the TgCRND8 mouse model. In conclusion, we demonstrate a significant inhibitory effect of Aβ on protein prenylation and identify SREBP-2 as a target of oAβ(42), directly linking Aβ to cholesterol homeostasis impairment.